El subsistema de la prescripción en el derecho administrativo - Catacora Santisteban, Percy Alberto (2018)
A legal figure of notable evolution is that of prescription, which is based on all laws of the world with variables in terms of time, the same that has been necessary starting from the administrative bases whose principle has been to request the prescription in the so-called : At the request of a party and not by decision of its own motion; In this context the figure of the prescription becomes a constitutional principle, whose analysis is necessary to ventilate in the different legal disciplines that are dictated in university courses, not only in the faculties of law, but also in others that in their curricular plans involve Disciplines without leaving aside the principle of prescription, this figure is not recent, but dates back to the early lusters of Roman times and is invoked under two scopes, one of prescription prescription and another of extinctive or liberatory prescription.